Bridging the Knowledge Gap on Rabies: A Cross-Sectional Study of General Practitioners’ Awareness and Clinical Management in Pakistan - Naveed Mansoori; Zohaib ur Rehman Mufti; Rashid Jamal; Imran Bakar; Rabia Yasmin; Syed Muhammad Mubeen (ANNALS OF ABBASI SHAHEED HOSPITAL AND KARACHI MEDICAL & DENTAL COLLEGE, 2026)
Objective: This study aimed to assess the knowledge regarding rabies and its management among general practitioners in Pakistan.Methods: This cross-sectional study was conducted from March to December 2023 among general practitioners practicing in public and private clinics or hospitals in different cities of Pakistan. Using non-probability convenient sampling technique, a pre-tested structured questionnaires was administered among GPs to assess the knowledge and practices regarding rabies and its management. Descriptive statistics for frequency and percentage were acquired for all variables. Continuous variables are presented as mean ± SD. Independent t-test was used to compare mean knowledge and practice score and its association with demographic variables. Data was analyzed by using SPSS version 24. A P value